Preparation method of ammonium ion intercalation hydrated layered vanadium oxide and application of ammonium ion intercalation hydrated layered vanadium oxide in aqueous zinc ion battery
By using ammonium ion intercalation hydrated layered vanadium oxide as the positive electrode material for zinc ion batteries, the problem of poor stability of vanadium-based cathode during circulation is solved, and efficient long-term circulation performance is achieved.
Patent Information
- Application Number
- CN202311137871.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-04
AI Technical Summary
The vanadium-based cathode encounters challenges such as dissolution and phase transition during the circulation of zinc ion batteries, resulting in its unsatisfactory long-term stability in practical applications.
The ammonium ion intercalation hydrated layered vanadium oxide ((NH4)0.4V2O5·nH2O) is used as the positive electrode material. The preparation method includes dispersing the pentavalent vanadium source compound and an inorganic substance containing ammonium ions in a mixed solution of water and organic solvent, adjusting the pH value, adding oxalic acid dihydrate and reacting at high temperature to obtain the vanadium-based oxide of the ammonium ion intercalation.
The hydrated layered vanadium oxide positive electrode sheet prepared by this method showed excellent long-term circulation performance in zinc ion batteries, and the capacity retention rate after 100 cycles was as high as 86%.
Smart Images

Figure HDA0004432475690000011 
Figure HDA0004432475690000012 
Figure HDA0004432475690000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of zinc ion batteries and relates to a preparation method of ammonium ion intercalated hydrated layered vanadium oxide and application of the same in a rechargeable zinc ion battery. Background Art
[0002] In recent years, since the Industrial Revolution, carbon dioxide emissions have increased year by year. The harm of carbon dioxide emissions is very extensive, not only affecting the natural ecology and human society, but also posing a threat to the development of the global economy and society. Therefore, we need to take effective measures to reduce carbon dioxide emissions to protect our earth's environment. For example, promoting clean energy, promoting energy conservation and efficient use, and strengthening environmental awareness are all effective measures we can take. Developing high-performance energy storage technology is the key.
[0003] Rechargeable aqueous zinc-ion batteries (ZIBs) using near-neutral aqueous electrolytes have emerged as promising solutions for large-scale energy storage due to their inherent safety, environmental friendliness, low cost, and high theoretical capacity. However, the commercialization of ZIBs technology requires significant progress in addressing existing scientific and technological gaps, especially in the field of cathode development. In addition, since cathode materials play a crucial role in determining the storage capacity and energy / power density of ZIBs, the choice of cathode materials directly affects the overall performance and capabilities of ZIBs, making it a key aspect in their design and optimization. Among various options (including manganese-based oxides, Prussian blue analogs, and organic compounds), vanadium-based compounds have attracted considerable attention as one of the most promising cathode materials for practical applications of ZIBs due to their high theoretical capacity, high power density, and long cycle life. In this context, a large amount of research work has been devoted to studying a wide variety of vanadium-based compounds, including anhydrous vanadium oxides, metal vanadates, vanadium phosphates, and other variants. However, despite their potential, vanadium-based cathodes encounter challenges such as dissolution and phase transition during cycling, resulting in unsatisfactory long-term stability in practical ZIBs. Addressing these issues and improving the stability of vanadium-based cathodes are critical to unlocking their full potential for reliable and efficient energy storage in ZIBs. Summary of the invention
[0004] The present invention aims to propose a solution for the synthesis of stable vanadium-based positive electrode materials in zinc ion batteries and the stable crystal structure during the charge and discharge process. To this end, the present invention systematically provides a method for preparing ammonium ion intercalated hydrated layered vanadium oxide and its application in rechargeable zinc ion batteries.
[0005] First, the present invention provides a method for preparing an ammonium ion intercalated hydrated layered vanadium oxide, wherein the chemical composition of the ammonium ion intercalated hydrated layered vanadium oxide is (NH4) 0.4V2O5·nH2O, wherein n is 0.01 to 2. The preparation method of the hydrated layered vanadium oxide comprises the following steps: firstly dispersing a pentavalent vanadium source compound and an inorganic substance containing ammonium ions in a mixed solution of water and an organic solvent; then adjusting the pH of the mixed solution to 1 to 5 with an appropriate amount of an acidic solution to obtain a precursor solution; then adding dihydrated oxalic acid to the precursor solution and reacting at 90 to 200°C for 5 to 20 hours; and obtaining a vanadium-based oxide intercalated with ammonium ions by centrifugation or filtration, washing and drying.
[0006] Furthermore, in the above technical solution, the pentavalent vanadium source compound is one or more of vanadium pentoxide and ammonium metavanadate; and the concentration of the pentavalent vanadium source compound is 0.01 to 1 mol / L.
[0007] Furthermore, in the above technical solution, the inorganic salt containing ammonium ions is one or more of ammonia water, (NH4)2SO4, NH4NO3, NH4Cl; and the concentration of the inorganic salt containing ammonium ions is 0.0001 to 1 mol / L.
[0008] Furthermore, in the above technical solution, the organic solvent is one or more of methanol, ethanol, ethylene glycol, isopropanol and dimethylformamide; and the volume ratio of the organic solvent to water is 0 to 2.
[0009] Furthermore, in the above technical solution, the acidic solution is one or more of hydrochloric acid, sulfuric acid, nitric acid, glacial acetic acid, and hydrogen peroxide.
[0010] Furthermore, in the above technical solution, the reaction temperature is 90-200°C, and the reaction time is 5-20h. The preferred reaction temperature is 120-140°C; the preferred reaction time is 5-10h.
[0011] The present invention provides an ammonium ion intercalation hydrated layered intercalated vanadium oxide prepared by the above method, which is used as the positive electrode of a zinc ion battery and has very excellent long-term cycle performance. The preparation steps of the zinc ion battery positive electrode sheet are: according to the hydrated layered vanadium oxide, activated carbon and polyvinylidene fluoride, they are dispersed in N-methylpyrrolidone, mixed evenly to form a slurry, applied to a current collector, and vacuum dried at 60 to 130°C for 5 to 48 hours to obtain a zinc ion battery positive electrode sheet.
[0012] Furthermore, in the above technical solution, the mass ratio of the hydrated layered vanadium oxide, activated carbon and polyvinylidene fluoride is (6-8):(1-3):1.
[0013] Furthermore, in the above technical solution, the current collector is a stainless steel mesh, a stainless steel foil, a titanium mesh or a titanium foil.
[0014] Furthermore, in the above technical solution, the loading amount of the active material of the positive electrode of the zinc ion battery is 0.5-10 mg cm -2 The preferred positive electrode active material loading is 1-5 mg cm -2 .
[0015] Furthermore, in the above technical solution, the vacuum drying temperature is 60-130°C, and the vacuum drying time is 5-48 hours. The preferred vacuum drying temperature is 90-120°C, and the preferred vacuum drying time is 10-24 hours.
[0016] Finally, the present invention provides a method of assembling a hydrated layered vanadium oxide positive electrode sheet in a zinc ion battery. The preparation steps of the zinc ion battery are as follows: placing the hydrated layered vanadium oxide positive electrode sheet and zinc foil in a battery shell, placing a diaphragm in the middle, adding an electrolyte containing zinc ions, and then packaging the battery. The packaged battery is connected to an electrochemical charge and discharge instrument, and a cycle performance test is performed at a specified current density. The obtained zinc ion battery exhibits excellent cycle stability.
[0017] Beneficial results:
[0018] The preparation method of the ammonium ion intercalated hydrated layered vanadium oxide requires simple equipment, is easy to operate, and has low cost. The X-ray diffraction (XRD) spectrum shows that the XRD spectrum of the hydrated layered vanadium oxide obtained by the present invention matches the standard XRD spectrum (see Figure 1 ). Scanning electron microscopy shows that the prepared hydrated layered vanadium oxide has a nanorod-like microstructure (see Figure 2 ). Zinc-ion batteries based on hydrated layered vanadium oxide cathodes have a high performance at 0.2A g -1 At a current density of 1.5 %, the specific capacity can reach 466 mAhg -1 (See Figure 3 ), the capacity retention rate after 100 cycles is still as high as 86% (see Figure 4 ). BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The present invention is attached Figure 5 Size:
[0020] Figure 1 The XRD spectrum of the ammonium ion intercalated hydrated layered vanadium oxide prepared in Example 1 and its standard spectrum
[0021] Figure 2 is a scanning electron microscope image of the ammonium ion intercalated hydrated layered vanadium oxide in Example 1;
[0022] Figure 3 It is a charge and discharge curve diagram of the zinc ion battery using ammonium ion intercalated hydrated layered vanadium oxide as the positive electrode in Example 1.
[0023] Figure 4 This is a long-term cycle performance diagram of the ammonium ion intercalated hydrated layered vanadium oxide as the positive electrode zinc ion battery in Example 1.
[0024] Figure 5 The XRD spectra of the ammonium ion intercalated hydrated layered vanadium oxides prepared in Examples 1 to 8 are shown. DETAILED DESCRIPTION
[0025] The present invention provides a method for preparing ammonium ion intercalated hydrated layered vanadium oxide, and the use of the hydrated layered vanadium oxide obtained by the method as a positive electrode material in a rechargeable zinc ion battery. The chemical composition of the hydrated layered vanadium oxide is (NH4) 0.4 V2O5·nH2O, wherein n is 0.01 to 2.
[0026] The following examples will further illustrate the present invention, but are not intended to limit the invention.
[0027] The preparation method of the hydrated layered vanadium oxide in the following Examples 1-9 comprises the following steps:
[0028] (1) A certain amount of pentavalent vanadium source compound is dispersed in a mixed solution of a certain amount of water and an organic solvent.
[0029] (2) Dissolving a certain amount of inorganic salt containing ammonium ions into the mixed solution of step (1).
[0030] (3) Add a certain amount of acidic solution to the mixed solution of step (2) and adjust the pH value to obtain a precursor solution.
[0031] (4) Adding a certain amount of oxalic acid dihydrate to the mixed solution of step (3).
[0032] (5) The precursor solution in step (4) is transferred to a stainless steel reactor lined with polytetrafluoroethylene and reacted at high temperature for a period of time.
[0033] (6) Centrifuging or filtering the turbid system in step (5), washing with water and ethanol, and drying to obtain a vanadium-based oxide.
[0034] The method for preparing the hydrated layered vanadium oxide positive electrode sheet in the following Examples 1-9 comprises the following steps:
[0035] (1) Weigh a certain amount of hydrated layered vanadium oxide, activated carbon and polyvinylidene fluoride.
[0036] (2) Add an appropriate amount of N-methylpyrrolidone and grind for 2 h to obtain a slurry.
[0037] (3) After the slurry is applied to the current collector, it is dried in a vacuum oven at a certain temperature for a period of time to obtain a layered vanadium oxide positive electrode sheet.
[0038] The preparation method of the zinc ion battery in the following embodiments 1-9 comprises the following steps:
[0039] The hydrated layered vanadium oxide positive electrode and the zinc foil negative electrode are placed in the battery case, with a glass fiber separator in the middle.
[0040] A ZnSO4 (2M) aqueous solution was added and then the battery was packaged to prepare a rechargeable zinc ion battery.
[0041] The performance of the zinc ion battery prepared in the embodiment of the present invention was further evaluated by testing its long-term cycle performance at a specific current density and an operating voltage range of 0.2V to 1.6V.
[0042] Example 1
[0043] Weigh 1.17g NH4VO3 in a beaker, add 70mL deionized water to obtain a yellow suspension, add 5 drops of concentrated hydrochloric acid to adjust the pH to 3 to obtain a precursor solution. Add 1.26g H2C2O4·2H2O, stir for 30min, then transfer the precursor solution to a reactor and react at 120℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark blue-green powder (NH4) 0.4 V2O5·nH2O. Its XRD spectrum is similar to the standard spectrum of hydrated layered vanadium oxide Figure 1 The dark blue powder is hydrated layered vanadium oxide. Scanning electron microscopy results show that the prepared hydrated layered vanadium oxide presents a nanorod-like microscopic morphology (see Figure 2 ). Weigh 0.15g dark blue powder, 0.03g conductive carbon black (Super P) and 0.02g XC-72 into a mortar, add 1mL N-methylpyrrolidone, and grind for 2h to mix evenly to obtain electrode slurry. Then apply the above electrode slurry on a stainless steel current collector with a diameter of 14mm and dry it in a vacuum oven at 100℃. The obtained positive electrode sheet is used to obtain a zinc ion battery according to the battery preparation method in the above invention content, and the battery performance is evaluated. The test results show that at a current density of 0.2A g -1 The specific capacity is 466 mAh g -1 (See Figure 3 ), the capacity retention rate after 100 cycles is still as high as 86% (see Figure 4 ).
[0044] Example 2
[0045] Weigh 1.17g NH4VO3 and 1mL ammonia water in a beaker, add 70mL deionized water to obtain a yellow suspension, add 5 drops of concentrated hydrochloric acid to adjust the pH to 3 to obtain a precursor solution. Add 1.26g H2C2O4·2H2O, stir for 30min, then transfer the precursor solution to the reactor and react at 120℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark blue-green powder. Its XRD spectrum is consistent with the standard spectrum of hydrated layered vanadium oxide. Figure 1 The dark blue powder is (NH4) 0.4 V2O5·nH2O. Scanning electron microscopy results show that the prepared hydrated layered vanadium oxide presents a nanorod-like microscopic morphology. The zinc sheet weighs 0.15g of dark blue powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 and puts them in a mortar, drops 1mL of N-methylpyrrolidone, and grinds for 2h to mix evenly to obtain an electrode slurry. Then the above electrode slurry is coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100℃. The obtained positive electrode sheet is used to obtain a zinc ion battery according to the battery preparation method in the above invention content, and the battery performance is evaluated.
[0046] Example 3
[0047] Weigh 1.17g NH4VO3 and 1g (NH4)2SO4 in a beaker, add 70mL deionized water to obtain a yellow suspension, add 5 drops of concentrated hydrochloric acid to adjust the pH to 3 to obtain a precursor solution. Add 1.26g H2C2O4·2H2O, stir for 30min, then transfer the precursor solution to a reactor and react at 120℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark blue-green powder (NH4) 0.4 V2O5·nH2O. Its XRD spectrum is similar to the standard spectrum of hydrated layered vanadium oxide Figure 1 The results of scanning electron microscopy showed that the prepared hydrated layered vanadium oxide showed a nanorod-like microscopic morphology. Weigh 0.15g of dark blue powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 into a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. Then, the above electrode slurry was coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100℃. The obtained positive electrode sheet was used to obtain a zinc ion battery according to the battery preparation method in the above invention content, and the battery performance was evaluated.
[0048] Example 4
[0049] Weigh 1.17g NH4VO3 and 1g NH4NO3 in a beaker, add 70mL deionized water to obtain a yellow suspension, add 5 drops of concentrated hydrochloric acid to adjust the pH to 3 to obtain a precursor solution. Add 1.26g H2C2O4·2H2O, stir for 30min, then transfer the precursor solution to a reactor and react at 120℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark blue-green powder (NH4) 0.4 V2O5·nH2O. Its XRD spectrum is similar to the standard spectrum of hydrated layered vanadium oxide Figure 1 The results of scanning electron microscopy showed that the prepared hydrated layered vanadium oxide showed a nanorod-like microscopic morphology. Weigh 0.15g of dark blue powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 into a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. Then, the above electrode slurry was coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100℃. The obtained positive electrode sheet was used to obtain a zinc ion battery according to the battery preparation method in the above invention content, and the battery performance was evaluated.
[0050] Example 5
[0051] Weigh 1.17g NH4VO3 and 1g NH4Cl in a beaker, add 70mL deionized water to obtain a yellow suspension, add 5 drops of concentrated hydrochloric acid to adjust the pH to 3 to obtain a precursor solution. Add 1.26g H2C2O4·2H2O, stir for 30min, then transfer the precursor solution to a reactor and react at 120℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark blue-green powder (NH4) 0.4 V2O5·nH2O. Its XRD spectrum is similar to the standard spectrum of hydrated layered vanadium oxide Figure 1 The results of scanning electron microscopy showed that the prepared hydrated layered vanadium oxide showed a nanorod-like microscopic morphology. Weigh 0.15g of dark blue powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 into a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. Then, the above electrode slurry was coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100℃. The obtained positive electrode sheet was used to obtain a zinc ion battery according to the battery preparation method in the above invention content, and the battery performance was evaluated.
[0052] Example 6
[0053] Weigh 0.36g V2O5 and 1g (NH4)2SO4 in a beaker, add 70mL deionized water to obtain a yellow suspension, add 5 drops of concentrated hydrochloric acid to adjust the pH to 3 to obtain a precursor solution. Add 1.26g H2C2O4·2H2O, stir for 30min, then transfer the precursor solution to a reactor and react at 120℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark blue-green powder (NH4) 0.4 V2O5·nH2O. Its XRD spectrum is similar to the standard spectrum of hydrated layered vanadium oxide Figure 1 The results of scanning electron microscopy showed that the prepared hydrated layered vanadium oxide showed a nanorod-like microscopic morphology. Weigh 0.15g of dark blue powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 into a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. Then, the above electrode slurry was coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100℃. The obtained positive electrode sheet was used to obtain a zinc ion battery according to the battery preparation method in the above invention content, and the battery performance was evaluated.
[0054] Example 7
[0055] Weigh 1.17g NH4VO3 in a beaker, add 70mL deionized water to obtain a yellow suspension, add 5 drops of concentrated nitric acid to adjust the pH to 3 to obtain a precursor solution. Add 1.26g H2C2O4·2H2O, stir for 30min, then transfer the precursor solution to a reactor and react at 120℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark blue-green powder (NH4) 0.4 V2O5·nH2O. Its XRD spectrum is similar to the standard spectrum of hydrated layered vanadium oxide Figure 1 The results of scanning electron microscopy showed that the prepared hydrated layered vanadium oxide showed a nanorod-like microscopic morphology. Weigh 0.15g of dark blue powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 into a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. Then, the above electrode slurry was coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100℃. The obtained positive electrode sheet was used to obtain a zinc ion battery according to the battery preparation method in the above invention content, and the battery performance was evaluated.
[0056] Example 8
[0057] Weigh 1.17g NH4VO3 in a beaker, add 70mL deionized water to obtain a yellow suspension, add 5 drops of concentrated sulfuric acid to adjust the pH to 3 to obtain a precursor solution. Add 1.26g H2C2O4·2H2O, stir for 30min, then transfer the precursor solution to a reactor and react at 120℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark blue-green powder (NH4) 0.4 V2O5·nH2O. Its XRD spectrum is similar to the standard spectrum of hydrated layered vanadium oxide Figure 1 The results of scanning electron microscopy showed that the prepared hydrated layered vanadium oxide showed a nanorod-like microscopic morphology. Weigh 0.15g of dark blue powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 into a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. Then, the above electrode slurry was coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100℃. The obtained positive electrode sheet was used to obtain a zinc ion battery according to the battery preparation method in the above invention content, and the battery performance was evaluated.
[0058] Example 9
[0059] Weigh 1.17g NH4VO3 in a beaker, add 70mL deionized water to obtain a yellow suspension, add 5 drops of concentrated hydrochloric acid to adjust the pH to 2.5 to obtain a precursor solution. Add 1.26g H2C2O4·2H2O, stir for 30min, then transfer the precursor solution to a reactor and react at 120℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark blue-green powder (NH4) 0.4 V2O5·nH2O. Its XRD spectrum is similar to the standard spectrum of hydrated layered vanadium oxide Figure 1 The results of scanning electron microscopy showed that the prepared hydrated layered vanadium oxide showed a nanorod-like microscopic morphology. Weigh 0.15g of dark blue powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 into a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. Then, the above electrode slurry was coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100℃. The obtained positive electrode sheet was used to obtain a zinc ion battery according to the battery preparation method in the above invention content, and the battery performance was evaluated.
[0060] Example 10
[0061] Weigh 1.17g NH4VO3 in a beaker, add 70mL deionized water to obtain a yellow suspension, add 5 drops of concentrated sulfuric acid to adjust the pH to 2 to obtain a precursor solution. Add 1.26g H2C2O4·2H2O, stir for 30min, then transfer the precursor solution to a reactor and react at 120℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark blue-green powder (NH4) 0.4 V2O5·nH2O. Its XRD spectrum is similar to the standard spectrum of hydrated layered vanadium oxide Figure 1 The results of scanning electron microscopy showed that the prepared hydrated layered vanadium oxide showed a nanorod-like microscopic morphology. Weigh 0.15g of dark blue powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 into a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. Then, the above electrode slurry was coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100℃. The obtained positive electrode sheet was used to obtain a zinc ion battery according to the battery preparation method in the above invention content, and the battery performance was evaluated.
[0062] Comparative Example 1
[0063] Weigh 1.17g NH4VO3 and 0.5g methylamine in a beaker, add 70mL deionized water to obtain a yellow suspension, add 5 drops of concentrated hydrochloric acid to adjust the pH to 3 to obtain a precursor solution. Add 1.26g H2C2O4·2H2O, stir for 30min, then transfer the precursor solution to a reactor and react at 120℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark blue-green powder (CH3NH2) x V2O5·nH2O. Its XRD spectrum is similar to the standard spectrum of hydrated layered vanadium oxide Figure 1 The results of scanning electron microscopy showed that the prepared hydrated layered vanadium oxide showed a nanorod-like microscopic morphology. Weigh 0.15g of dark blue powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 into a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. Then, the above electrode slurry was coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100℃. The obtained positive electrode sheet was used to obtain a zinc ion battery according to the battery preparation method in the above invention content, and the battery performance was evaluated.
[0064] Comparative Example 2
[0065] Weigh 1.17g NH4VO3 and 0.5g ethylamine in a beaker, add 70mL deionized water to obtain a yellow suspension, add 5 drops of concentrated hydrochloric acid to adjust the pH to 3 to obtain a precursor solution. Add 1.26g H2C2O4·2H2O, stir for 30min, then transfer the precursor solution to a reactor and react at 120℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark blue-green powder (C2H5NH2) x V2O5·nH2O. Its XRD spectrum is similar to the standard spectrum of hydrated layered vanadium oxide Figure 1 The results of scanning electron microscopy showed that the prepared hydrated layered vanadium oxide showed a nanorod-like microscopic morphology. Weigh 0.15g of dark blue powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 into a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. Then, the above electrode slurry was coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100℃. The obtained positive electrode sheet was used to obtain a zinc ion battery according to the battery preparation method in the above invention content, and the battery performance was evaluated.
[0066] Comparative Example 3
[0067] Weigh 1.17g NH4VO3 and 0.5g ethylenediamine in a beaker, add 70mL deionized water to obtain a yellow suspension, add 5 drops of concentrated hydrochloric acid to adjust the pH to 3 to obtain a precursor solution. Add 1.26g H2C2O4·2H2O, stir for 30min, then transfer the precursor solution to a reactor and react at 120℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark blue-green powder (C2H4N2H4) x V2O5·nH2O. Its XRD spectrum is similar to the standard spectrum of hydrated layered vanadium oxide Figure 1 The results of scanning electron microscopy showed that the prepared hydrated layered vanadium oxide showed a nanorod-like microscopic morphology. Weigh 0.15g of dark blue powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 into a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. Then, the above electrode slurry was coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100℃. The obtained positive electrode sheet was used to obtain a zinc ion battery according to the battery preparation method in the above invention content, and the battery performance was evaluated.
Claims
1. A method for preparing ammonium ion intercalated hydrated layered vanadium oxide, characterized in that: The chemical composition of the hydrated layered vanadium oxide is (NH4) 0.4 V2O5·nH2O, wherein n is 0.01-2; the preparation method comprises the following steps: firstly, dispersing a pentavalent vanadium source compound and an inorganic substance containing ammonium ions in a mixed solution of water and an organic solvent; then adjusting the pH of the mixed solution to 1-5 with an appropriate amount of an acidic solution to obtain a precursor solution; then adding dihydrated oxalic acid to the precursor solution, and then reacting the precursor solution at a certain temperature for a period of time; reacting at 90-200°C for 5-20h; and obtaining a vanadium-based oxide with ammonium ion intercalation through centrifugation or filtration, washing and drying.
2. The preparation method according to claim 1, characterized in that: The pentavalent vanadium source compound is selected from one or more of vanadium pentoxide and ammonium metavanadate; the concentration of the pentavalent vanadium source compound is 0.01-1 mol / L.
3. The preparation method according to claim 1, characterized in that: The inorganic substance of ammonium ion is selected from one or more of ammonia water, (NH4)2SO4, NH4NO3, NH4Cl; the total ion concentration of the ammonium ion is 0.01-1 mol / L.
4. The preparation method according to claim 1, characterized in that: The organic solvent is one or more of methanol, ethanol, ethylene glycol, isopropanol and dimethylformamide; the volume ratio of the organic solvent to water is 0-2.
5. The preparation method according to claim 1, characterized in that: The acidic solution is one or more of hydrochloric acid, sulfuric acid, nitric acid, glacial acetic acid, and hydrogen peroxide.
6. The preparation method according to claim 1, characterized in that: The precursor reaction temperature is 90-200° C., and the reaction time is 5-20 hours.
7. Use of the ammonium ion intercalated hydrated layered vanadium oxide obtained according to the preparation method of claim 1 in a rechargeable zinc ion battery, wherein the ammonium ion intercalated hydrated layered vanadium oxide is used as a positive electrode material of a rechargeable zinc ion battery to prepare a rechargeable zinc ion battery.
8. The use according to claim 7, characterized in that: The preparation steps of the rechargeable zinc ion battery positive electrode material are as follows: hydrated layered vanadium oxide, activated carbon and polyvinylidene fluoride are dispersed in N-methylpyrrolidone, mixed evenly to form a slurry, applied to a current collector, and vacuum dried at 60-130° C. for 5-48 hours to obtain a positive electrode sheet; the mass ratio of the ammonium ion intercalated hydrated layered vanadium oxide, activated carbon and polyvinylidene fluoride is (6-8): (1-3): 1; the current collector is a stainless steel mesh, stainless steel foil, titanium mesh or titanium foil; the loading amount of the active material of the zinc ion battery positive electrode sheet is 0.5-10 mg cm -2 .
9. The use according to claim 7, characterized in that: The preparation steps of the zinc ion battery are to place the ammonium ion intercalated hydrated layered vanadium oxide positive electrode sheet and zinc foil in a battery shell, put a separator in the middle, add an electrolyte containing zinc ions, and then package the battery.
Citation Information
Cited By
Oxygen vacancy-containing ammonium ion intercalation vanadium oxide as well as preparation method and application thereof
CN120553755A